A Antropologia Estrutural de Lévi-Strauss e suas reverberações geográficas - Cláudio Luiz Zanotelli (Confins)
The article analyzes the possible interrelationship between geography and structural anthropology. It focuses in particular on the relationship between culture and nature and society - space. It is observed that the structural method developed by Claude Lévi- Strauss allows us to associate the outer space to inner space of man, dealing with the sensitive immanent form and intelligible. Thus the structuralist method appears to be of great fertility to the geographic method and understanding of the environment in interaction with society in a dialectical process.